Measuring customer perceptions index using CMAC speech emotion mapping - Kamaruddin, Norhaslinda; Abdul Rahman, Abdul Wahab (IEEE Computer Society, 2014)
Customer perception is very important in ensuring the positive feedbacks and endurance of a product or service in the market. Marketers conduct customer satisfaction survey to measure customer's need, expectation and experience through multiple instruments; such as verbal and written survey. In this paper, an exploratory approach of speech emotion mapping using cerebellum model articulation controller is proposed to gauge respondents' perception index through telephone survey. Experimental results show that such approach has a potential to be used as an alternative tool to discriminate respondents' perception.